Education Initiative for Essential Conversations with Parents—Serious Illness Guide for Pediatrics (SICG-Peds©-Peds) - Camara van Breemen; Nadine Lusney; Megan Doherty; Elisa Castro-Noriega; Harold (Hal) Siden (Journal of Medical Education and Curricular Development)
Objectives To explore whether training on the SICG-Peds© (Serious Illness Guide for Pediatrics) impacts a pediatric clinician's confidence and knowledge in participating and initiating/leading difficult conversations with families of children living with a serious illness. Methods Over 2 years, clinicians from BC and Ontario who care for children with serious illnesses attended training workshops on the SICG-Peds©. These workshops were evaluated using pre- and post-workshop questionnaires. Participants reported confidence scores on a scale of 1 to 10. Results In total, 134 and 140 clinicians attended the workshops in BC and Ontario, respectively. The majority of clinicians who completed the immediate post-workshop survey ( N  = 223, 94.5%), responded that the content enhanced their knowledge about pediatric serious illness conversations (SIC). Confidence scores in initiating/leading a SIC significantly increased from median 5 (interquartile range [IQR] 3-7) pre-workshop to 7 (IQR 7-9) immediately post-workshop ( P  < .0001). Confidence scores in participating as a non-leader in a SIC also significantly increased from median 7 (IQR 6-9) pre-workshop to median 8 (IQR 7-9) immediately post-workshop ( P  < .0001). Conclusions Overall, these workshops significantly improved participants’ confidence. Effectiveness and knowledge enhancement were other areas where the majority of participants reported positive improvements. Areas for continued support were identified as more mentoring, and training for supporting the guide's use in a clinical setting.